Prevalence and Pattern of Congenital Malformations among Neonates in the Neonatal Unit of a Tertiary Care Hospital - Zabit Khan Naibzai, Abeera Afzal Buzdar, Maham Khalid, Najma Fatima, Nimra Khalid, Zarmast Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Globally, congenital anomalies (CA) are a major contributing factor for neonate’s admission in NICU causing neonatal morbidity and mortality particularly in developing countries. Congenital anomalies generally indicate the morphogenesis defect in an early neonate’s life. The leading cause for perinatal mortality is congenital anomalies that arise with advancement of delivery and care for newborn babies. The present study aimed to evaluate the prevalence and pattern of congenital anomalies among neonates admitted to neonatal unit. Methodology: This retrospective study was carried out on 1620 neonates (newborns to age 28 days) admitted to the neonatal unit of Services Hospital, Lahore from April 2020 to March 2022. The incidence, risk factors, and pattern of congenital anomalies were measured. Detailed examinations such as radiological, laboratory, ultrasonography, and echocardiography were recorded. Different outcomes such as hospital stay, morbidity, and mortality were determined with 95% confidence intervals. SPSS version 25 was used for data analysis. Results: Of the total 1620 admitted neonates, the prevalence of neonates with congenital anomalies were 112 (6.9%). Out of 112 neonates diagnosed with congenital anomalies, 64 (57.1%) were male and 48 (42.9%) were females. The incidence of cesarean and other modes of delivery were 74 (66%) and 38 (34%) respectively. Cardiovascular system malformation was the most prevalent affected system in 36 (31.9%) neonates followed by central nerve system 28 (25%), genitourinary system 19 (17%), musculoskeletal system 16 (14.3%), gastrointestinal tract 6 (5.4%), digestive system 4 (3.6%), and syndromes and skin 3 (2.7%). Congenital anomalies were significantly increasing over time. The incidence of discharged, referred to higher centers for intervention, and expired babies were 77 (68.8%), 19 (16.7%), and 16 (14.3%) respectively. Conclusion: The present study found that the prevalence of congenital anomalies was 6.9%. Cardiovascular system malformation was the most prevalent congenital anomaly followed by the central nerve system. The overall mortality rate was 14.3% caused by congenital anomalies. A better health care strategies and management must be developed in terms of early detection, supplementation facilitation, decreasing drug usage, and better antenatal care to prevent the impacts of congenital anomalies on neonates. Keywords: Prevalence, Pattern, Congenital anomalies, neonates